Increasing Creative and Innovative Thinking Ability through The Strengthening of Character Education in Probability Theory Course - Ahmad Yani T.; Sayaka Oikawa (STKIP Singkawang, 2019)
The purpose of this study was how to improve the ability to think creatively and innovatively through strengthening character education in the probability theory course. The sample of this study was 29 students of the fifth-semester of Mathematics Education. The method of research experimented, and the form of analysis is quasi-experimental. Data collection techniques are measurement techniques, creative and innovative thinking skills test and character education scale. The results increase in the ability of creative and innovative thinking through strengthening character education by providing learning in religious character education, being responsible both in groups and individually, discipline, honesty, tolerance for others, hard work, independence, having a high sense of curiosity in solving a problem related to Probability Theory.